Profil Tingkat Resiliensi Siswa Berdasarkan Jenis Kelamin Serta Implikasinya dalam Pelayanan Bimbingan dan Konseling - Delano, Vasco; Sinta Dewi, Eneng; Septarinjani, Hernindya; Arrumaisyah Daulay, Annisa (Universitas PGRI Palembang, 2025)
This study aims to describe the level of student resilience in terms of gender and its implications in guidance and counseling services. The study used a quantitative approach with a descriptive-comparative method. The study population was students of SMAN 3 Padang City and SMAN 3 Mukomuko with a sample size of 278 students, consisting of 121 males and 157 females selected through proportional random sampling techniques. The research instrument was a resilience scale that had been tested for validity and reliability. The results showed that in general the level of resilience of male students was higher than that of females, with an average resilience score of male students of 70.95% and females of 69.10%, both in the high category. Significant differences were found in the sub-variables of optimism and emotional regulation. These findings indicate that gender is a factor that influences students' ability to deal with post-disaster stress and trauma. The implications of these results direct BK teachers to design gender-responsive guidance services in order to maintain and improve students' psychological resilience in schools.